Algorithm and peer‐to‐peer negotiation strategies for train dispatching problems in railway bottleneck sections. Issue 11 (13th September 2019) - Liu, Jin; Chen, Lei; Roberts, Clive; Nicholson, Gemma; Ai, Bo
Abstract : Train delays occur often in daily railway operations due to a variety of initiating incidents. On a heavily loaded mainline railway, a single train delay may lead to a series of secondary delays across the network. In this study, the authors describe a peer‐to‐peer system to solve train rescheduling problems in railway network bottlenecks. A designed Genetic Algorithm is chosen as the local search algorithm on each side. Based on the local search algorithm, different negotiation protocols are raised to find globally feasible solutions. The proposed approach is tested in a railway bottleneck section in the UK, and the computational result is compared with a centralised method to show its performance in terms of computation time and optimality.